Water erosion in no-tillage monoculture and intercropped systems along contour lines - Ildegardis Bertol; Roger Robert Ramos; Fabrício Tondello Barbosa; Antonio Paz González; Julio César Ramos; Douglas Henrique Bandeira (Revista Brasileira de Ciência do Solo, 2013)
Water erosion is the major cause of soil and water losses and the main factor of degradation of agricultural areas. The objective of this work was to quantify pluvial water erosion from an untilled soil with crop rows along the contour, in 2009 and 2010, on a Humic Dystrupept, with the following treatments: a) maize monoculture; b) soybean monoculture; c) common bean monoculture; d) intercropped maize and bean, exposed to four simulated rainfall tests of on hour at controlled intensity (64 mm h-1). The first test was applied 18 days after sowing and the others; 39, 75 and 120 days after the first test. The crop type influenced soil loss through water erosion in the simulated rainfall tests 3 and 4; soybean was most effective in erosion control in test 3, however, in test 4, maize was more effective. Water loss was influenced by the crop type in test 3 only, where maize and soybean were equally effective, with less runoff than from the other crops. The soil loss rate varied during the runoff sampling period in different ways, demonstrating a positive linear relationship between soil and water loss, in the different rainfall tests.